Development of a Decision-Making System for Sultan Moulay Slimane University in Beni Mellal, Morocco - Abdellah Amine; Rachid Ait Daoud; Belaid Bouikhalene (Institute of Advanced Engineering and Science, 2016)
The issue dealt with in this article is to develop a decision-making information system related to the digital environment of the University work. We propose to model the data within the university in order to transform a system of information into a decision-making information system, that is based on the trades databases oriented toward the actors. A decision-making information is a system that allows the decision makers of the university to have relevant information and powerful analytical tools to help them take the right decision at the right time.